PEMBERDAYAAN MASYARAKAT BERBASIS ASET KOMUNITAS - Didiet Widiowati (Journal of Social and Political Science)
This research entitled "Assets-based Community development in Gedepangrango Village Kadudampit sub-district Sukabumi District". The Poor Family in Gedepangrango Village is 68.53%. This problem of poverty causes other social problems such as baby neglected, children neglected, neglected elderly, Children With disabilities (ADK), Persons With disabilities (ODK), Women Prone Social Economics (PRSE), etc.. On the other side, Desa Gedepangrango is rich in community assets that can be optimized to empower communities in an effort to overcome poverty. The purpose of this research is to produce Assets-based Community development design in Gedepangrango Village, Kadudampit Sub-district, Sukabumi District. The research method used qualitative method, with action research type (Action Research). The data sources are Village Apparatus, Community Leaders and community of Gedepangrango Village, selected purposively. Data Collection Techniques use indepth Interviews, Participatory Observation, Documentation Studies and Focus Group Discussion (FGD). The results show that in Gedepangrango Village there are assets based namely physical assets, financial assets, human assets, environmental assets, social assets, technology assets, and spiritual assets. Through social intervention (physical development, economic development, and social development), social workers as facilitators optimize assets based in an effort to empower communities to address poverty and other social problems. This research also produces Assets-based Community development design. Keywords: Assets-based, Ecological Perspective, community development, Poverty, Strengths Perspective,